Household food security and nutritional status among early adolescent: a cross sectional study in urban slums of Dhaka, Bangladesh. - Poudyal, Anil (2016)
Abstract: Background: Early adolescence between the age of 10 -14 years is an important period of life, in which youth undergo varied and rapid physical, cognitive, and social transformation. Unique nutritional needs and demand of these years set a foundation for a healthily adult life. Most research among this age group has focused on adolescent females and therefore both sexes is important to include in this study. There are 1.2 billion adolescents globally of whom 90% reside in developing nations and around half of them are stunted. Hunger and chronic malnutrition in Bangladesh remains highest in the world where 1 in 4 household populations have no regular access to sufficient, safe and nutritious food. Food security and nutrition are essential component of sustainable development; however one in every nine people in the world is suffering from hunger and malnutrition. This cross-sectional study tries to explore different socio demographic factors affecting the household food security and nutritional status among early adolescent 10 - 14 years old living in urban slums of Dhaka, Bangladesh. Objective: To determine the association between household food security and nutritional status among early adolescent 10 -14 years old living in urban slums of Dhaka, Bangladesh. Method: A cross sectional study was done in urban slum of Dhaka. Quantitative approach was employed to assess the association between food security and nutritional status of early adolescent at a specific time. Data were collected using the Household Food Insecurity Access Scale (HFIAS) tool. Households were quantified as food secure, mildly food insecure access, moderately food insecure access, and severely food insecure access based on their responses. Nutritional status of early adolescent were calculated by Z score using three reference value of height for age, Weight for age, and BMI for age. Result: A total of 370 early adolescent of both gender were surveyed. Our study found that majority of household, about fourth fifth 82.43%, were food insecure where higher percentage 38.65% were severe food-insecure, followed by moderately and mildly 33.51 % and 10.57% respectively. Only 17.57% of household were food secure. Almost more than one fourth 28.7% of the respondents were low BMI for age where 31.8% of adolescent had stunted (low height for age Z score) and 34.18% were underweight /wasted (low weight for age Z- score). Our findings showed there was no relationship between household food security and nutritional status of early adolescent. Conclusion: High prevalence of under nutrition and household food insecurity was found in three different urban slum of Dhaka. Finding of this result strongly recommended the emphasis on nutritional intervention on the priority basis. Government should acknowledge the issue of urban food insecurity with providing short and long term measure for food security program.